Life Science Case Examples Using the Quick Screen Tool for Opportunity Assessments - Friedrich, Ryan; Lee, Joon Seok; Salih, Rayan K.; Boni, Arthur A.; York, John M. (American Journal of Management, 2024)
Innovations are plentiful in the biopharma landscape but often fail to reach commercialization. This paper addresses the research question: How can a tool efficiently assess life science opportunities to go to market successfully? This paper analyzes three case studies using the quick screen tool, culminating in a scorecard that reflects commercial potential and readiness. COASTAR’s score of 1.95 represents strong potential despite lacking clinical validation, while JD Bioscience’s score of 2.87 reflects unique attributes and developmental risks. Reviva’s score of 3.08 highlights strong intellectual property and competitive challenges. The quick screen tool simplifies decision-making, with simple rules enhancing heuristic strategies.